ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG PADA AKSEPTOR KB AKTIF DALAM PROGRAM KAMPUNG KB (STUDI KASUS DI KAMPUNG KB KOTA SEMARANG) - Larisa Rizki; Besar Tirto Husodo; Syamsulhuda BM (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
One of the success output indicator program of family planning village in anticipation of a drop out use of contraceptive methods and to control the population growth is the achievement of target Long Term use of Contraceptive Methods (MKJP) in a village. At the end of 2017, there were ten family palnning villages in the city of Semarang that had not reached the target. This study aims to analyze behaviour using MKJP’s on active users in the program of family planning village. The research used cross sectional study design. The population in this study were all active family planning acceptors in 16 areas family planning villages of Semarang City and the sample was taken by simple random sampling technique which amounted to 92 people. Data analysis using univariate, bivariate and multivariate analysis. The results of this study indicate that more than half of respondents had good behavior in using MKJP in the program of family planning villages Semarang (55.4%). The results of chi square tests showed that there was a significant relationship between age (p=0.002), parity ( p=0.037), smallest child age (p=0.000), participation in contraceptive use (p=0.004), type of contraception (p=0,000), time of contraception installation (p=0,000), purpose of contraceptive use (p=0,000), knowledge (p=0,002), husband's support (p=0,002), and availability of information (p=0,040) with usage MKJP in active family planning acceptors. The multiple logistic regression test showed that smallest child age was the most influenced variable (OR=5,961). Therefore, the skills of health workers related to contraception must be increased, for active family planning acceptors are expected to play an active role in every activity in the village of family planning related to contraception especially MKJP and the related sectors expected to increase community knowledge and do clarification on myths about MKJP